A New Noninvasive Method in Evaluating the Endothelial Function: The Measurement of the Resistive Index after Reactive Hyperemia of the Brachial Artery - Korkmaz, Hasan; Akbulut, Mehmet; Ozbay, Yilmaz; Koc, Mustafa (Wiley-Blackwell, 2010)
Objective: The objective of our study was to investigate whether the measurement of the resistive index (RI) after reactive hyperemia is a relevant method for the evaluation of the endothelial function. Materials and methods: 54 hypertensive patients and 27 controls were prospectively enrolled for the study. In addition to the flow-mediated dilation (FMD), the RI was also measured during the same procedure. RI is a vascular resistance parameter that is most commonly used to minimize the intra- and interobserver variability because of its reliability among repeated measurements. The percent change of the RI after reactive hyperemia (HRI) in comparison to the baseline RI was defined as the flow-mediated RI (FMRI). (FMRI = 100 x [HRI - baseline RI/baseline RI]). Results: The groups were comparable in terms of age, sex, and left ventricular ejection fraction. Differences were present in the systolic arterial pressure (mmHg; 161 +/- 15 vs. 114 +/- 7, P = 0.000), diastolic arterial pressure (mmHg; 96 +/- 7 vs. 72 +/- 7, P = 0.000) and left ventricular mass index (g/m2; 124 +/- 5 vs. 99 +/- 6, P = 0.002). As expected, the FMD differed significantly between hypertensive and control groups (4 +/- 4% vs. 13 +/- 12%, respectively; P = 0.000). There was also a significant difference in the FMRI values between the groups (-21 +/- 10; -30 +/- 14, P = 0.002). FMD and FMRI values were negatively correlated (P < 0.05). Conclusion: For the noninvasive evaluation of the endothelial function, FMRI value measured as RI value after reactive hyperemia can be a good alternative to the FMD measured as vascular diameter after reactive hyperemia. (Echocardiography 2010;27:873-877).
Keywords: resistive index; flow-mediated dilation; endothelial function